PENGARUH MEDIA PEMBELAJARAN FLASH CARD BERBASIS TEKA-TEKI SILANG TERHADAP HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPAS - Barus, Florensya Br; Tanjung, Darinda Sofia; HS, Dyan Wulan Sari; Silalahi, Eka Kartika Silalahi; Purba, Frikson (Universitas Negeri Medan, 2025)
This research aimed to determine the effect of crossword puzzle-based flash card learning media on the learning outcomes of fifth-grade students in IPAS subject. The study was conducted at UPT. SDN 060938 Medan using a quantitative approach with a one-group pretest-posttest design. The subject consisted of 27 fifth-grade students. Data collection involved learning outcomes tests and questionnaires. Data analysis included correlation tests and t-tests. The results showed that the flash card media significantly improved learning outcomes, with a posttest average of 89.07 and a correlation coefficient of 0.938. The t-test yielded tcount = 13.576 > ttable = 3.707, indicating a significant and positive influence of the media on students' IPAS learning outcomes.